Highly (001)-oriented zirconium-doped ceria films grown on biaxially textured nickel tungsten substrates through an inorganic-salts-based chemical solution deposition route. Issue 13 (September 2018) - Lei, Li; Li, Limin; Wang, Shasha; Jia, Jiqiang; Zhao, Gaoyang; Oshima, Yoshifumi; Jin, Lihua; Wang, Yao; Li, Chengshan; Zhang, Pingxiang
Abstract: In this work, Zr-doped CeO2 (Ce1-x Zrx O2, CZO) films with (001) preferential orientation were fabricated on biaxially textured NiW alloy substrates by using a novel sol-gel method. The precursor solutions were synthesized through a newly developed process using common inorganic metal salts of Zr and Ce as the starting materials instead of organic salts. The influence of annealing temperature and the Ce/Zr mole ratio in the precursor solutions on the growth texture of CZO films was investigated. The precursor solutions with the concentration of 0.3 mol/L were coated on the Ni5W substrates using a dip-coating method and then heat-treated at 1050 °C for an hour under a reducing atmosphere of high-purity Ar with 5 vol% H2 . The CZO thin films show excellent c-axis preferential orientation when the content of Zr in CZO thin film is less than 40%. The full width of half maximum of the phi scan of (111) reflection and omega scan of (200) reflection of CZO films is as low as the value of about 5° and 6°, respectively. Moreover, it is found that the inside of CZO thin film exhibits quite dense and uniform without cracks and porosity with the aid of the scanning transmission electron microscopy analysis by which the epitaxial growth relationship of (220)CZO // (200)NiW between CZO and NiW is simultaneously confirmed. Finally, highly (00  l )-oriented YBCO film with good superconducting properties was deposited on CZO buffered NiW substrate. The above results indicate that the CZO film is a quite promising candidate of single buffer layer architecture for YBCO coated conductor.